Relationship between Work Posture and Symptoms of Musculoskeletal Disorders in Rice Farmers - Muhammad Akbar Salcha; Arni Juliani (Universitas Mandala Waluya, 2021)
The agricultural sector has a fairly high health risk due to exposure to wrong work postures. The purpose of this study was to determine the relationship between work posture and symptoms of musculoskeletal disorders (MSDs) in farmers in Lembang Nonongan Village, Sopai District, North Toraja Regency. This type of research is an analytic observational study with a cross sectional design. The sampling method is exhaustive sampling, with a total sample of 43 people. Data were collected using the Rapid Entire Body Assessment (REBA) sheet to measure work posture and the Nordic Body Map (NBM) sheet to measure the level of respondents' complaints. This study was analyzed using the chi square test with a 95% confidence degree (α=0.05). The results of this study indicate that the majority of rice farmers experience symptoms of MSDs with severe complaints as many as 31 people (72.1%) and work postures with high risk as many as 35 people (81.4%). There is a significant relationship between work posture and symptoms of MSDS (p-value=0.028). It is recommended that farmers when carrying out the process of lifting rice sacks that have a heavy load to use assistive devices so as not to exacerbate the high risk of MSDs.